Cardiac Metastasis of a Low‐Grade Myofibroblastic Sarcoma. Issue 1 (24th September 2013) - Oylumlu, Muhammed; Yildiz, Abdulkadir; Ercan, Suleyman; Oylumlu, Mustafa; Davutoglu, Vedat
Mini‐Abstract We present a case of low‐grade myofibroblastic sarcoma arising from inguinal region accompanied by cardiac metastasis. A 36‐year‐old male patient suffering from recurrent inguinal swelling was operated. Initial evaluation mistakenly diagnosed the condition as benign. During follow‐up, recurrence of mass revealed a low‐grade myofibroblastic sarcoma. Echocardiographic screening in patients with noncardiac myofibroblastic sarcomas may be helpful in detecting silent metastases before development of cardiac symptoms in terms and may offer prognostic information. This is first report of a low‐grade myofibroblastic sarcoma to metastasize to myocardium. Cardiac metastasis of a sarcoma might have rapid progression of the disease with fatal course.